Machining of Micro-holes on Sodalime Glass Using Developed Micro-abrasive Jet Machine (μ-AJM). (2016) - Kumar, Abhishek; Hiremath, Somashekhar S.
Abstract: Micro abrasive jet machining is a non-conventional machining process used to produce micro features such as holes, channels on various brittle materials in particular and engineering materials in general. This process finds wide industrial applications. This paper investigates the optimal machining parameters to machine holes on sodalime glass for multiple performance characteristics. Grey Relational Analysis (GRA) is used for optimizing the process parameters for the material removal rate (MRR) and radial overcut (ROC). Air pressure, stand-off distance and abrasive mess are selected as the machining parameters. Taguchi Orthogonal L9 array is used to design the experiments. Based on the grey relational grades obtained for the experimental runs, optimization of process parameters have been carried out and the obtained results are presented in the paper. The results include holes size, material removal rate and radial overcut.